PEMETAAN PROSES BISNIS AS-IS DALAM MANAJEMEN LAYANAN TOEIC INSTITUSI VOKASI - Narti Prihartini (LPPM Universitas Putera Batam, 2023)
The Ministry of Communication and Informatics has established a Business Process Map for Ministry Level on Level zero (0) up to level 3 and this applies to organizations up to the work unit level. The requirement to prepare supporting facilities in English language test services can improve student competences. It become one of the core businesses of UPT Bahasa in Sambas State Polytechnic with some repetitive processes, so that it is necessary to simplify the existing business process maps. Mapping of AS-IS business process is needed to help determine priorities from TOEIC implementation flow. Based on the running system, there are 13 major processes in the implementation of the TOEIC in the institution with duration for approximately 4 weeks. It is ineffective because only one test period can be held at a time. Depend on those conditions, the mapping of business process activities is needed to define AS-IS business process to give brief explanation about the running system and find the right solution to prepare system optimalization to define the TO-BE Business Process. This research is succeed to provide the mapping of AS-IS Business Process of TOEIC Service Management and determine the mapping level from level 0 to level 3.